2007
DOI: 10.1002/pon.1192
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of specific risk factors for insomnia in women treated for early‐stage breast cancer

Abstract: Background-Many individual risk factors for insomnia have been identified for women with a history of breast cancer. We assessed the relative importance of a wide range of risk factors for insomnia in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
87
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 84 publications
(114 reference statements)
14
87
3
8
Order By: Relevance
“…Though the prevalence ranges vary depending on the study characteristics, cancer survivors have consistently reported higher rates of sleep problems compared than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which parallel with our findings. Notwithstanding the limits of knowledge on the exact mechanism across the cancer trajectory, cancer-related sleep problems covering difficulties initiating or maintaining sleep, dissatisfaction with sleep quality, and/or short sleep duration appear to begin with cancer diagnosis, inducing emotional challenges (i.e., anxiety and distress), and are easily exacerbated during cancer treatments such as chemotherapy, which continue through cancer survivorship (Palesh et al, 2012;Garland et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Though the prevalence ranges vary depending on the study characteristics, cancer survivors have consistently reported higher rates of sleep problems compared than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which parallel with our findings. Notwithstanding the limits of knowledge on the exact mechanism across the cancer trajectory, cancer-related sleep problems covering difficulties initiating or maintaining sleep, dissatisfaction with sleep quality, and/or short sleep duration appear to begin with cancer diagnosis, inducing emotional challenges (i.e., anxiety and distress), and are easily exacerbated during cancer treatments such as chemotherapy, which continue through cancer survivorship (Palesh et al, 2012;Garland et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Other cancer-related somatic symptoms (i.e., fatigue, nausea, and diarrhea), psychological distress, and depression can also interrupt the sleeping patterns in cancer patients (Garland et al, 2014). Furthermore, emerging evidence has indicated that these negative consequences accompanied with cancer diagnosis may persist during long-term survivorship: many of cancer survivors have reported symptoms of insomnia and undergone sleep disturbance more likely than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which can progress to an increased risk for morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between education and sleep disturbance in breast cancer patients has not been consistent across studies [34,39,40]. Nevertheless, our findings may reflect the fact that more educated women may have better knowledge regarding breast cancer prognosis and treatment-related disability that can contribute to minimize the physical and psychological impact of cancer diagnosis and cancer treatment on sleep quality.…”
Section: Discussioncontrasting
confidence: 49%
“…Finally, through a systematic review, Brown et al confirm the association of fatigue with depression and anxiety but emphasize the need of longitudinal studies to better delineate its directionality [33]. Previous results described a tendency for higher levels of sleep disturbance in women submitted to radiotherapy when compared to those not submitted to this type of treatment, though results were not statistically significant [26,27,34]. We found a nearly fourfold higher risk of poor sleep quality among women submitted to the highest doses of radiotherapy; the impact of physical side effects of radiation, such as skin reactions and pain, which have been demonstrated to increase with the dose administered [35], could be precipitating factors for sleep disturbances in those with good sleep quality prior to treatment.…”
Section: Discussionmentioning
confidence: 86%
“…59 Rather, worse physical health, less exercise, and more depressive symptoms were the risk factors most strongly linked with fatigue in these women who had completed initial treatment within the previous four years. 59 Thus, the evidence linking mood disturbance and cancer-related fatigue is variable. It is difficult to tease out the effects of the medical illness versus those of mood symptoms on fatigue in the chronically medically ill. 24,54 Nonetheless, the fact that four out of five breast cancer patients with cancer-related fatigue do not experience a concurrent major depressive disorder suggests that mood and fatigue in cancer are overlapping but far from fully redundant concepts.…”
Section: Depressionmentioning
confidence: 99%